Cyanobacteria and Alphaproteobacteria May Facilitate Cooperative Interactions in Niche Communities - Van Goethem, Marc W.; Makhalanyane, Thulani P.; Cowan, Don A.; Valverde, Angel (Frontiers in Microbiology, 2017)
Hypoliths, microbial assemblages found below translucent rocks, provide important ecosystem services in deserts. While several studies have assessed microbial diversity of hot desert hypoliths and whether these communities are metabolically active, the interactions among taxa remain unclear. Here, we assessed the structure, diversity and co-occurrence patterns of hypolithic communities from the hyperarid Namib Desert by comparing total (DNA) and potentially-active (RNA) communities. The potentially-active and total hypolithic communities differed in their composition and diversity, with significantly higher levels of Cyanobacteria and Alphaproteobacteria in potentially-active hypoliths. Several phyla known to be abundant in total hypolithic communities were metabolically inactive, indicating that some hypolithic taxa may be dormant or dead. The potentially-active hypolith network was highly modular in structure with almost exclusively positive co-occurrences (>95% of the total) between taxa. Members of the Cyanobacteria and Alphaproteobacteria were identified as potential keystone taxa, and exhibited numerous positive co-occurrences with other microbes, suggesting that these groups might have important roles in maintaining network topological structure despite their low abundance.